Charity work of the Y.M.C.A. - Dille, Alfred Burton (My University, 1899)
Introduction: In studying the different epochs of history, we find each one characterized by some particular event- many of which have lived throughout all ages, and others which have flourished for a time, then decayed. One which has continued to exist and grow stronger and more complex each succeeding year is that of Christianity; and this growth in complexity has caused various departments to arise, all following after one ideal. Not many years ago, a new departure was taken along this line, aiming at the harmonious development of the three essentials which make a perfect man- Body, Mind, and Spirit. Such a work was undertaken by the young men of the land, and termed the “Young Men’s Christian Association.” One of the various and, it seems to me, the most important divisions of this Association is that for the relief of young men in need of help- the Charity work.
Citation: Dille, Alfred Burton. Charity work of the Y.M.C.A. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Charity Work; Care of the Sick; Advantages of a Private Hospital; Theses; Manuscripts (documents)